Papel da reforma e modernização militar para a grande estratégia da China - Gomes, Thaísy Caroline Guedes (2019)
In the contemporary international scene, the significant increase in the power and influence of the People's Republic of China, in recent decades, has raised questions and interests of other international actors about what China's real intentions are. The country's steady economic growth provides the resources needed to sustain the ambition of the “Chinese Dream” of rejuvenation. This rejuvenation is in line with the current Chinese military modernization and reform, which aims to build a strong military force capable of defending the interests and objectives of China's Great Strategy. Therefore, this paper proposes a case study focusing on the People's Republic of China, on the hypothesis that military modernization and reform plays an important role to ensure the goals and interests of China's great strategy. Highlighting important points in the formation of the China’s Great Strategy and the main procedures taken by Xi Jinping towards the creation of a modern armed force capable of placing itself among the other military powers of the XIX century. From this study it’s noticeable the imperative importance of the military component to the Great Strategy of China.